Induction of Labour in Prelabour Rupture of Membranes with or without Cervical Ripening with Prostaglandin E2: A Randomized Controlled Trial - Aryal, Shreyashi; Karki, Chandra (Journal of Lumbini Medical College, 2016)
Objective: To compare the outcome of induction of labour with titrated dose of oxytocin with or without pre induction cervical ripening using prostaglandin E2.Methods: This is a prospective study. Sixty women with prelabour rupture of membranes (PROM) and Bishops score of less than six were randomly assigned to either immediate induction with intravenous oxytocin drip or induction with intravenous oxytocin drip preceded by cervical priming with prostaglandin E2 (PGE2) gel 0.5mg instilled intracervically. These two groups were compared regarding the mode of delivery, induction to delivery interval and maternal and neonatal morbidities.Results: Cervical priming with PGE2 resulted in lesser number of caesarean section (5 Vs. 12) and lower incidence of meconium stained liquor (n=6 Vs. n=2). Induction to vaginal delivery interval was shorter when cervical priming was done (5.4 hrs Vs 7.9 hrs). The maternal morbidity was negligible (